2012
DOI: 10.1111/j.1464-5491.2012.03641.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemoglobin A1c, acute hyperglycaemia and short‐term prognosis in patients without diabetes following acute ST‐segment elevation myocardial infarction

Abstract: Unlike acute hyperglycaemia, an elevated HbA(1c) level was not a risk factor for short-term outcomes in ST-segment elevation myocardial infarction patients without diabetes. Patients with acute hyperglycaemia and non-elevated HbA(1c) were associated with the worst prognosis. That suggests chronic glycaemic control/HbA(1c) level may help to recognize stress-induced hyperglycaemia and identify high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 29 publications
1
21
0
2
Order By: Relevance
“…The value showed that the association between HbA 1c level and 30-day mortality were not significant when the cut-off value was 6.5%. It was noteworthy that all of the five studies [3,8,12,25,27] in the 6.5% group were conducted in Asia. As mentioned above, HbA 1c might not have significant prognostic value among Asian STEMI patients (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The value showed that the association between HbA 1c level and 30-day mortality were not significant when the cut-off value was 6.5%. It was noteworthy that all of the five studies [3,8,12,25,27] in the 6.5% group were conducted in Asia. As mentioned above, HbA 1c might not have significant prognostic value among Asian STEMI patients (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Results from previous studies were controversial [3,8,[10][11][12][13][14]. Considering the different management and treatment strategies [15], the effects that high HbA 1c level have on STEMI patients might differ from other types of CAD.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although several previous studies showed conflicting results on the association between HbA1c and both short and long term mortality in STEMI patients with or without diabetes 3,18,20,21 , only 1 study to date has assessed the association between HbA1c and LV dysfunction on echocardiography. Salmasi and co-workers evaluated HbA1c and transmitral M A N U S C R I P T…”
Section: Glycated Hemoglobin and Left Ventricular Dysfunction After Smentioning
confidence: 99%